Foreign exchange exposure : Japanese multinational corporations from 1994-2004. - Loy, Yvonne Mei Chee. (2008)
We investigate the exchange rate exposure effects of 206 Japanese multinational firms selected based on a minimum export ratio of 10 percent during the period 1994 to 2004.